1999
DOI: 10.1111/j.1365-2621.1999.tb15941.x
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1 Production and Growth of Fusarium moniliforme and Fusarium proliferatum on Maize, Wheat, and Barley Grain

Abstract: Two isolates each of Fusarium moniliforme and Fusarium proliferatum isolated from maize were compared for growth and fumonisin B 1 production on maize, wheat, and barley extract agars and on irradiated maize, wheat, and barley grain in relation to water availability and temperature. Growth rates of both Fusarium spp. were similar or higher on wheat and barley than on maize extract agar. Regardless of temperature, all isolates produced fumonisin B 1 only on irradiated maize grain, but not on wheat or barley. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 18 publications
5
41
1
1
Order By: Relevance
“…Sporadic reports on contamination of wheat grains with FB 1 are found in literature (STANKOVIC et al, 2012). According to MARIN et al (1999), the reason for this low occurrence in barley and wheat may be due to the presence of competing mycobiota (which are quite different from maize), which may inhibit the synthesis of fumonisins by Fusarium sp., or degrade the mycotoxin soon after being produced. Furthermore, according to the authors, several nutritional components in wheat could act as inhibitors of the biosynthesis by fumonisins.…”
Section: Resultsmentioning
confidence: 99%
“…Sporadic reports on contamination of wheat grains with FB 1 are found in literature (STANKOVIC et al, 2012). According to MARIN et al (1999), the reason for this low occurrence in barley and wheat may be due to the presence of competing mycobiota (which are quite different from maize), which may inhibit the synthesis of fumonisins by Fusarium sp., or degrade the mycotoxin soon after being produced. Furthermore, according to the authors, several nutritional components in wheat could act as inhibitors of the biosynthesis by fumonisins.…”
Section: Resultsmentioning
confidence: 99%
“…Fumonisins are produced optimally between 20 and 30°C and water activity (a w ) between 0.955 and 0.990 and ceases below 10°C and at a w lower than 0.930 (Marín et al, 1999). FUM1 and FUM19 transcripts were observed from F. verticillioides cultures incubated at 20°C for 14 days and found to be linearly correlated to fumonisin production (López-Errasquín et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Sporulation, germination, and growth of F. verticillioides are optimised at 25-30 °C (Maiorano et al, 2009;Rossi et al, 2009). Most studies have found optimal conditions for fumonisin production are a temperature close to 30 °C and high water activity (Marin et al, 1999;Reid et al, 1999). However, optimal conditions for fumonisin production by F. proliferatum appear to be significantly different, with a lower optimal temperature (Marin et al, 1999).…”
mentioning
confidence: 99%
“…Some models are based on laboratory studies describing the effects of environmental conditions such as temperature and water activity on the production of mycotoxins (Marin et al, 1999), and these can be used as a basis for field models. Other models are based on data collected from field studies, or developed by validating laboratory results in the field.…”
mentioning
confidence: 99%